Anti-N-Methyl-d-Aspartate Receptor Encephalitis - Te-Yu Hung; Ning-Hui Foo; Ming-Chi Lai (Elsevier, 2011)
Anti-N-methyl-d-aspartate (NMDA) receptor encephalitis is a treatment-responsive encephalitis associated with anti-NMDA receptor antibodies, which bind to the NR1/NR2 heteromers of the NMDA receptors. It is a highly characteristic syndrome evolving in five stages: the prodromal phase (viral infection-like symptoms), psychotic phase, unresponsive phase, hyperkinetic phase, and gradual recovery phase. It has been considered as a paraneoplastic syndrome usually affecting childbearing-age female with ovarian tumors; however, recent reports suggest a much higher incidence of nonparaneoplastic cases in children. We report a 14-year-old girl with anti-NMDA receptor encephalitis without a detectable tumor who showed a nearly complete recovery after intensive immunotherapy.